2000
DOI: 10.1038/35014530
|View full text |Cite
|
Sign up to set email alerts
|

Rossby waves on the Sun as revealed by solar ‘hills’

Abstract: It is a long-standing puzzle that the Sun's photosphere--its visible surface--rotates differentially, with the equatorial regions rotating faster than the poles. It has been suggested that waves analogous to terrestrial Rossby waves, and known as r-mode oscillations, could explain the Sun's differential rotation: Rossby waves are seen in the oceans as large-scale (hundreds of kilometres) variations of sea-surface height (5-cm-high waves), which propagate slowly either east or west (they could take tens of year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 13 publications
6
64
1
Order By: Relevance
“…In any case, the Rieger-group periodicities are found in the coronal X-ray emission data, which confirms the existence of a global process that gives rise to the escape of magnetic flux from sub-photospheric regions through the solar atmosphere to the outer heliosphere. Using SOHO/MDI data, Kuhn et al (2000) reported the surface manifestation of Rossby waves. If the presences of r-mode or Rossby types of waves are assumed in the Sun, then the families of periods begot by the dispersion relation of these waves are…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the Rieger-group periodicities are found in the coronal X-ray emission data, which confirms the existence of a global process that gives rise to the escape of magnetic flux from sub-photospheric regions through the solar atmosphere to the outer heliosphere. Using SOHO/MDI data, Kuhn et al (2000) reported the surface manifestation of Rossby waves. If the presences of r-mode or Rossby types of waves are assumed in the Sun, then the families of periods begot by the dispersion relation of these waves are…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Rossby waves have been observed in the terrestrial oceans as largescale variations of sea-surface height with amplitudes ≤10 cm and wavelengths ≥500 km (Chelton & Schlax 1996). Kuhn et al (2000) have reported the detection of 100 m high "hills" in the solar photosphere, spaced uniformly over the solar surface with a characteristic separation of approximately 90 000 km (corresponding to m ≈ 50). These observations were made with the Michelson Doppler Imager (MDI) on board the Solar and Heliospheric Observatory (SOHO) and interpreted as the photospheric signature of long-period r-modes.…”
Section: Possible R-mode Signatures In the Magnetic Fluxmentioning
confidence: 99%
“…Moreover, Lou has also pointed out that such waves can give rise to detectable features, such as surface elevations in the photosphere. Coincidently, Kuhn et al (2000) have reported observations made with the Michelson Doppler Imager (MDI) on board SOHO and claim to have detected a regular structure of 100 m "" hills,ÏÏ uniformly spaced over the surface of the Sun with a characteristic separation of 90,000 km. They suggest that this structure is the surface manifestation of Rossby waves, or r-modes oscillations.…”
Section: Introductionmentioning
confidence: 99%